Effect of couplet care on early parent–infant closeness among preterm infants - Itoshima, Ryo; Korhonen, Kalle; Axelin, Anna; Ahlqvist‐Björkroth, Sari; Hovi, Anna; Lehtonen, Liisa (Wiley, 2025)
Aim
To evaluate the effect of couplet care on parent–infant closeness among preterm infants.
Methods
A comparison study in a Level III neonatal intensive care unit (NICU) before and after the introduction of couplet care, including stabilising infants in the delivery unit for early skin-to-skin contact, providing mothers' postpartum care in the infant's room and providing the father's bed in the infant's room. The study included parents of preterm infants born below 35 weeks.
Results
Parents of 40 and 66 infants were included before and after couplet care was introduced, respectively. In the linear regression model, the first skin-to-skin contact happened significantly earlier after the introduction than before: mean 4.0 vs. 24.0 h after birth and mean difference −18.5 (95% confidence interval −34.8 to −2.1). A larger proportion of infants received their first skin-to-skin contact within 2 h after birth after the introduction than before (45.5% vs. 8.6%; odds ratio 13.8 [3.6–62.8]). At least one parent was present in the infant's NICU room longer after the introduction than before (mean 21.2 vs. 10.8 h per day; mean difference 10.8 [9.1–12.4]).
Conclusion
Couplet care significantly increased parent–infant closeness during the first weeks of life.